2019
DOI: 10.3390/medicina55100664
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Thermal Ablation versus Open Partial Nephrectomy for the Treatment of Small Renal Tumors in Patients Over 70 Years Old

Abstract: Background and objectives: Microwave thermal ablation (MWT) is one of the treatment options for kidney cancer. However, for patients over 70 years old the safety and oncological efficacy of this treatment is still controversial. The goal of this study was to compare MWT with open partial nephrectomy (OPN) and to find out whether MWT is preferable in maintaining patient renal function and reducing the risk of postoperative complications. Materials and Methods: Depending on the treatment choice, all patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Anglickis et al compared the efficacy of microwave thermal ablation (MWT) with open partial nephrectomy (OPN) in the treatment of small renal tumors patients over 70 years old in the period between January 2012 and January 2019 in Lithuania. In their report, they found that MWT was the more advantageous method overall (assessed by the pain level reported by the patients after surgery (p = 0.008), hospitalization, and operation time (p < 0.001)), while there were no differences seen in oncological data and the blood loss-estimated glomerular filtration rate [38]. Augliené et al assessed the survival rate of renal grafts from cadavers in a tertiary-care center in Lithuania over a 7-year period (2007)(2008)(2009)(2010)(2011)(2012)(2013), which included the data analysis of n = 186 renal transplant patients.…”
mentioning
confidence: 96%
“…Anglickis et al compared the efficacy of microwave thermal ablation (MWT) with open partial nephrectomy (OPN) in the treatment of small renal tumors patients over 70 years old in the period between January 2012 and January 2019 in Lithuania. In their report, they found that MWT was the more advantageous method overall (assessed by the pain level reported by the patients after surgery (p = 0.008), hospitalization, and operation time (p < 0.001)), while there were no differences seen in oncological data and the blood loss-estimated glomerular filtration rate [38]. Augliené et al assessed the survival rate of renal grafts from cadavers in a tertiary-care center in Lithuania over a 7-year period (2007)(2008)(2009)(2010)(2011)(2012)(2013), which included the data analysis of n = 186 renal transplant patients.…”
mentioning
confidence: 96%